2008
DOI: 10.1523/jneurosci.5001-07.2008
|View full text |Cite
|
Sign up to set email alerts
|

Human Hippocampal and Parahippocampal Theta during Goal-Directed Spatial Navigation Predicts Performance on a Virtual Morris Water Maze

Abstract: The hippocampus and parahippocampal cortices exhibit theta oscillations during spatial navigation in animals and humans, and in the former are thought to mediate spatial memory formation. Functional specificity of human hippocampal theta, however, is unclear. Neuromagnetic activity was recorded with a whole-head 275-channel magnetoencephalographic (MEG) system as healthy participants navigated to a hidden platform in a virtual reality Morris water maze. MEG data were analyzed for underlying oscillatory sources… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

34
205
1
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(242 citation statements)
references
References 51 publications
34
205
1
2
Order By: Relevance
“…This is consistent with other MEG experiments evaluating memory and spatial navigation which have also reported hippocampal effects at slower theta frequencies (Cornwell et al, 2008;Kaplan et al, 2012;Staudigl and Hanslmayr, 2013). Although it has been suggested that the hippocampus may form a closed electric field due to its sym metrical morphology (Lorente de No, 1947), this would require that the entire structure be simultaneously activated, a rather unlikely sce nario under typical experimental conditions.…”
Section: Successful Reconstruction Of Slow Theta Sources In the Hipposupporting
confidence: 90%
See 2 more Smart Citations
“…This is consistent with other MEG experiments evaluating memory and spatial navigation which have also reported hippocampal effects at slower theta frequencies (Cornwell et al, 2008;Kaplan et al, 2012;Staudigl and Hanslmayr, 2013). Although it has been suggested that the hippocampus may form a closed electric field due to its sym metrical morphology (Lorente de No, 1947), this would require that the entire structure be simultaneously activated, a rather unlikely sce nario under typical experimental conditions.…”
Section: Successful Reconstruction Of Slow Theta Sources In the Hipposupporting
confidence: 90%
“…Here, we investigated the relationship between hippocampal slow theta activity and subsequent spatial memory accuracy in navigation. Although previous MEG studies evaluating subsequent navigation performance seem to support this hypothesis (Cornwell et al, 2008;Kaplan et al, 2012), slow theta activity related to the forma tion of item location associations during navigation has not been directly assessed until now. To make this possible, we administered the navigation task in the form of a subsequent memory paradigm where pictures of buildings were presented at particular spatial loca tions in a virtual grass field.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…These report reconstructed sources of theta within hippocampal (or parahippocampal) structures during task performance (Tesche & Karhu, 2000;Cornwell et al, 2008). Given that source reconstruction models suffer from important limitations in detecting sources in deep brain structures with a close geometry (Alarcon et al 1994;Wiederin et al 1999) these results are unconvincing.…”
Section: Discussionmentioning
confidence: 99%
“…The hippocampus and parahippocampal cortices exhibit theta oscillations during spatial navigation in rodents that are thought to mediate spatial memory formation. Neuromagnetic activity was recorded with a wholehead 275-channel magnetoencephalographic system as healthy participants navigated to a hidden platform in a virtual reality Morris water maze [91]. Analysis revealed greater theta activity in the left anterior hippocampus and parahippocampal cortices during goal-directed navigation relative to aimless movements in a sensorimotor control condition.…”
Section: Comparing Memory Island To Traditional Spatial Tests Of Humamentioning
confidence: 99%